Factors Associated with Diabetic Ulcer Prevention Behavior in Patients with Type 2 Diabetes Mellitus - Sari, Yoan Permata; Sari, Nova Nurwinda; Stiexs, Anggie (Inspirasi Foundation, 2026)
Introduction: Diabetes mellitus is a major non-communicable disease with a rapidly increasing prevalence and is associated with serious complications, including diabetic foot ulcers that contribute to disability and mortality. Preventive behaviors, particularly proper foot care, play a crucial role in reducing the risk of diabetic ulcers; however, these behaviors are influenced by various individual and contextual factors that require further investigation. Objective: Type 2 diabetes mellitus often causes macrovascular and microvascular complications, Macrovascular complications are more caused by hyperglycemia, hypoglycemia, diabetic nephropathy, diabetic neuropathy, and diabetic ulcers. The appearance of diabetic foot wounds is characterized by the presence of open wounds on the surface of the skin so that it results in infection due to the entry of germs or bacteria to the surface of the wound if not treated immediately, the infection will expand to the lower skin tissue, tendons, muscles, and even bones. This study aims to determine the factors related to diabetic ulcer prevention behavior in type 2 diabetes mellitus patients at the Kedaton Health Center Bandar Lampung. Method: The type of quantitative research with a cross sectional, sampling technique purposive research design with population 109 a sample of 86 respondents. The data analysis used was univariate and bivariate analysis using the chi square test. Result: The results of this study found that there was a relationship between knowledge and ulcer prevention behavior with a p-value of 0.000 (p-value < 0.05); there was a relationship between attitude and diabetic ulcer prevention behavior with a p-value of 0.000 (p-value < 0.05); and there was a long-standing relationship between suffering from DM and diabetic ulcer prevention behavior with a p-value of 0.022 (p-value < 0.05) at the Kedaton Health Center Bandar Lampung. Conclusion: People with diabetes mellitus should know and practice diabetic ulcer such as good and proper foot care prevention behaviors in order to prevent complications, especially diabetic wounds.